Effect of Bone Morphogenetic Protein Receptor-1B (BMPR-1B) Gene Variant on Litter Size in Akkaraman Sheep Breed - Acı, Recai; Duman, Esra; Kul, Selim; Yiğit, Serbülent (Universitas Airlangga, 2024)
The BMPR-1B gene, a significant fertility gene, has been examined for its relationship with fertility characteristics in various sheep populations globally. This investigation explored the impact of the BMPR-1B gene on litter size within the Akkaraman sheep population residing in the Elâzığ Region. To locate the FecB gene in Akkaraman sheep, 104 milk samples were collected, and genetic material was isolated using the salting out technique. During the 2021–2022 period, no significant correlations were observed between the genetic make-up of Akkaraman sheep and factors including age, mastitis and disease history, milk yield, birthing type, and the number of births (p > 0.05). However, there was a noteworthy relationship identified between the distribution of genetic make-up and live weight, indicating a potential influence of genetics on the live weight of Akkaraman sheep (p < 0.05). In this study, the BMPR-1B gene determined multiple births and it was determined that Akkaraman sheep were monomorphic in terms of this gene. In light of this information, it was concluded that more comprehensive studies should be carried out regarding this gene determining multiple births in the Akkaraman sheep breed.